2015
DOI: 10.1109/tap.2014.2382114
|View full text |Cite
|
Sign up to set email alerts
|

An Algebraic Solution Method for Nonlinear Inverse Scattering

Abstract: By using properly designed synthetic (or "virtual") experiments and an original approximation of the contrast sources, we are able to recast the inverse scattering problem in an algebraic form (in a subset of points of the imaged domain) and, hence, to solve it by means of closed form formulas. The new approximation relies on the assumption that the contrast sources induced by the different virtual experiments are focused in given points belonging to the scatterer. As such, the method involves a preprocessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In [6][7][8][9][10][11], the design of the VE exploits the integral equation at the core of LSM. To recall this procedure, let us introduce the far-field operator [1]:…”
Section: The Virtual Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [6][7][8][9][10][11], the design of the VE exploits the integral equation at the core of LSM. To recall this procedure, let us introduce the far-field operator [1]:…”
Section: The Virtual Experimentsmentioning
confidence: 99%
“…In a recent series of papers [6][7][8][9][10][11], it has been shown that it is possible to take advantage of the information achieved from the LSM not only to estimate the unknown target's support, but also to introduce new quantitative inversion methods. These latter are capable of retrieving the electromagnetic parameters of the unknown targets using linear approximations that hold true for non-weak scatterers [6,7], localized non-linear approximations [8] or new regularization schemes [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14], [16] and [17], [18] such a concept has been used to devise new approximations for the internal fields and the contrast sources, respectively, and exploited to cast new approximated inversion methods capable of working well beyond traditional linear approximations. In [15], the field approximation used in [14] was instead exploited as a convenient starting guess for a field-based MG inversion scheme.…”
Section: Measured Informationmentioning
confidence: 99%
“…The proposed strategy relies on an emerging paradigm for microwave imaging, which consists in taking advantage of experiments that are designed in such a way to enforce some specific behavior of the field or of the contrast source which generate this field [14]- [18]. Notably, these experiments are implemented in a synthetic way, that is, without performing additional measurements, but simply processing the available ones.…”
Section: Introductionmentioning
confidence: 99%